Paper 1  Objectives  49 Questions
JAMB Exam
Year: 1992
Level: SHS
Time:
Type: Question Paper
Answers provided
No description provided
This paper is yet to be rated
These are the three things to do in test preparation for higher grades and excellent performance.
11 hot tips for highest score in IELTS 2022 [ get band 8 or 9] Reading, Listening, Writing and speaking
IrelandAfrica Fellows Program 2023/2024 Postgraduate Scholarship for Young Africans free scholarship
#  Question  Ans 

1. 
Find n if 34_{n} = 10011_{2} A. 5 B. 6 C. 7 D. 8
Show Content
Detailed SolutionTo find n if 34n = 10011_{2}, convert both sides to base 10= 3n + 4 = (1 x 2^{4}) + (0 x2^{3}) + (0 x 2^{2}) + (1 x 2^{1}) + 1 x 2^{o} = 3n + 4 = 16 + 0 + 0 + 2 + 1 3n + 4 = 19 3n = 15 n = 5 

2. 
The radius of a circle is given as 5cm subject to an error of 0.1cm. What is the percentage error in the area of the circle? A. \(\frac{1}{25}\) B. \(\frac{1}{4}\) C. 4 D. 25
Show Content
Detailed Solution% error in Area = \(\frac{\pi(5.1)^2  \pi(5)^2 \times 100%}{\pi(5)^2}\)= \(\frac{\pi 26.01  25 \times 100%}{\pi(25)}\) = \(\frac{1.01}{25}\) x 100% = 4.04% 

3. 
Evaluate \(\log_{b} a^{n}\) if \(b = a^{\frac{1}{n}}\). A. n^{2} B. n C. \(\frac{1}{n}\) D. \(\frac{1}{n^2}\)
Show Content
Detailed SolutionLet \(\log_{b} a^{n} = x\)\(\therefore a^{n} = b^{x}\) \(a^{n} = (a^{\frac{1}{n}})^{x}\) \(a^{n} = a^{\frac{x}{n}} \implies n = \frac{x}{n}\) \(x = n^{2}\) 

4. 
What is the value of x satisfying the equation \(\frac{4^{2x}}{4^{3x}}\) = 2? A. 2 B. \(\frac{1}{2}\) C. \(\frac{1}{2}\) D. 2
Show Content
Detailed Solution\(\frac{4^{2x}}{4^{3x}}\) = 24^{2x  3x} = 2 4^{x} = 2 (2^{2})^{x} = 2^{1} Equating coefficients: 2x = 1 x = \(\frac{1}{2}\) 

5. 
Simplify \(\frac{(1.25 \times 10^{4}) \times (2.0 \times 10^{1})}{(6.25 \times 10^5)}\) A. 4.0 x 10^{3} B. 5.0 x 10^{2} C. 2.0 x 10^{1} D. 5.0 x 10^{3}
Show Content
Detailed Solution\(\frac{(1.25 \times 10^{4}) \times (2.0 \times 10^{1})}{(6.25 \times 10^5)}\) = \(\frac{1.25 \times 2}{6.25}\) x 10^{4  1  5}\(\frac{2.50}{6.25}\) x 10^{2} = \(\frac{250}{625}\) x 10^{2} 0.4 x 10^{2} = 4.0 x 10^{3} 

6. 
Simplify 5\(\sqrt{18}\)  3\(\sqrt{72}\) + 4\(\sqrt{50}\) A. 17\(\sqrt{4}\) B. 4\(\sqrt{17}\) C. 17\(\sqrt{2}\) D. 12\(\sqrt{4}\)
Show Content
Detailed Solution5\(\sqrt{18}\)  3\(\sqrt{72}\) + 4\(\sqrt{50}\) = 5(3\(\sqrt{2}\))  3(6\(\sqrt{2}\)) + 4(5\(\sqrt{2}\))15\(\sqrt{2}\)  18\(\sqrt{2}\) + 20\(\sqrt{2}\) = 35\(\sqrt{2}\)  18\(\sqrt{2}\) = 17\(\sqrt{2}\) 

7. 
If x = 3  \(\sqrt{3}\), find x^{2} + \(\frac{36}{x^2}\) A. 9 B. 18 C. 24 D. 27
Show Content
Detailed Solutionx = 3  \(\sqrt{3}\)x^{2} = (3  \(\sqrt{3}\))^{2} = 9 + 3  6\(\sqrt{34}\) = 12  6\(\sqrt{3}\) = 6(2  \(\sqrt{3}\)) ∴ x^{2} + \(\frac{36}{x^2}\) = 6(2  \(\sqrt{3}\)) + \(\frac{36}{6(2  \sqrt{3})}\) 6(2  \(\sqrt{3}\)) + \(\frac{6}{2  \sqrt{3}}\) = 6( \(\sqrt{3}\)) + \(\frac{6(2 + \sqrt{3})}{(2  \sqrt{3})(2 + \sqrt{3})}\) = 6(2  \(\sqrt{3}\)) + \(\frac{6(2 + \sqrt{3})}{4  3}\) 6(2  \(\sqrt{3}\)) + 6(2 + \(\sqrt{3}\)) = 12 + 12 = 24 

8. 
If x = (all prime factors of 44) and y = (all prime factors of 60), the elements of X ∪ Y and X ∩ Y respectively are A. (2, 4, 3, 5, 11) and (4) B. (4, 3, 5, 11) and (3, 4) C. (2, 5, 11) and (2) D. (2, 3, 5, 11) and (2)
Show Content
Detailed Solutionx = (all prime factors of 44) and y = (all prime factors of 60)∴ x = (2, 11), y = (2, 3, 5) X ∪ Y = (2, 3, 5, 11), X ∩ Y = (2) 

9. 
If U = (1, 2, 3, 6, 7, 8, 9, 10) is the universal set. E = (10, 4, 6, 8, 10) and F = {x: 1x\(^{2}\) = 2\(^{6}, x is odd}. Find (E ∩ F)', where ' means the complement of a set. A. (0) B. U C. (8) D. \(\phi\)
Show Content
Detailed SolutionU = (1, 2, 3, 6, 7, 8, 9, 10)E = (10, 4, 6, 8, 10) F = (x : x\(^2\) = 2\(^6\), x is odd) ∴ F = \(\phi\) Since x\(^2\) = 2\(^6\) = 64 x = \(\pm 8\) which is even ∴ E ∩ F = \(\phi\) Since there are no common elements 

10. 
Factorize \(9p^2  q^2 + 6qr  9r^2\) A. (3p  3q + r)(3p  q  3r) B. (6p  3q  3r)(3p  q  4r) C. (3p  q + 3r)(3p + q  3r) D. (3q  p + 3r)(3q  p + 3r)
Show Content
Detailed Solution\(9p^{2}  q^{2} + 6qr  9r^{2}\)= \(9p^{2}  (q^{2}  6qr + 9r^{2})\) = \(9p^{2}  (q^{2}  3qr  3qr + 9r^{2})\) = \(9p^{2}  (q(q  3r)  3r(q  3r))\) = \(9p^{2}  (q  3r)^{2}\) = \((3p + (q  3r))(3p  (q  3r))\) = \((3p + q  3r)(3p  q + 3r)\) 
Preview displays only 10 out of the 49 Questions